Collaborative Governance in Handling Public Complaints to the President at the Ministry of State Secretariat - Harahap, Haswan Boris Muda; Suradinta, Ermaya; Maryani, Dedeh; Averus, Ahmad (Universitas Medan Area, 2023)
The handling of public complaints on all types of problems generally falls under the authority of the relevant agencies to resolve them, so that collaboration with relevant agencies is needed in handling public complaints to the President. This study aims to analyze the handling of public complaints against the President based on the Collaborative Governance theory and model that has been running so far and to build a collaborative governance model design that is needed in handling public complaints. This research methodology uses qualitative data with primary sources of interviews, observations, and group discussions. The secondary data was obtained through various documents and literature studies. The results of the study show that Collaborative Governance in handling public complaints to the President at the Ministry of State Secretariat is not yet optimal because the main dimension of Institutional Design in the form of a legal framework that serves as a guideline in collaborative handling of public complaints to the President is not yet available. Researchers formulate Regulated Collaborative Governance which emphasizes the importance of compiling an Institutional Design before starting the collaboration process. The Regulated Collaborative Governance model is a modification of the Collaborative Governance model proposed by Ansell and Gash.